2010
DOI: 10.1016/j.surfcoat.2010.08.126
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property relations in ZrCN coatings for tribological applications

Abstract: ZrCN coatings were deposited by dc reactive magnetron sputtering with N 2 flows ranging from 2 to 10 sccm in order to investigate the influence of the nitrogen incorporation on structure and properties. Information about the chemical composition was obtained by glow discharge optical emission spectroscopy and Rutherford backscattering spectroscopy. The evolution of the crystal structure studied by X-ray diffraction revealed the formation of a face-centred cubic ZrCN phase for N 2 flows greater than 4 sccm. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 52 publications
3
49
0
Order By: Relevance
“…Further increasing of the Ag/Ti ratio leads to a noticeable hardness reduction, in spite of the maximum in the compressive residual stress, mainly attributed to the increasing presence of either a boundary amorphous carbon-based phases (a-C and CN x ) or silver nanoparticles that softens the film structure as it was stated in previous studies [22,30]. By using the deconvolution of phases plotted in Moreover, the continuous increase on the Ag/Ti atomic ratio induces the nucleation of silver, a soft metal, which also contributes to further diminution of the hardness.…”
Section: Mechanical Properties: Hardness and Residual Stressmentioning
confidence: 67%
“…Further increasing of the Ag/Ti ratio leads to a noticeable hardness reduction, in spite of the maximum in the compressive residual stress, mainly attributed to the increasing presence of either a boundary amorphous carbon-based phases (a-C and CN x ) or silver nanoparticles that softens the film structure as it was stated in previous studies [22,30]. By using the deconvolution of phases plotted in Moreover, the continuous increase on the Ag/Ti atomic ratio induces the nucleation of silver, a soft metal, which also contributes to further diminution of the hardness.…”
Section: Mechanical Properties: Hardness and Residual Stressmentioning
confidence: 67%
“…The reacting oxygen probably comes from the inevitable outgassing of the walls of the vacuum system for high annealing temperatures which provides steam oxygen in the vacuum chamber atmosphere. In the literature, the presence of zirconium oxide is still observed in zirconium films deposited by PVD whatever the vacuum used during the operation of the depositing [12,22,[26][27][28], and after vacuum annealing of bulk zirconium [29]. S.-W. Yeh et al showed that the deposition under a vacuum of 6.7×10 -2 Pa, leads to the formation of zirconium oxide for a 350°C substrate temperature.…”
Section: Xrd Analysismentioning
confidence: 99%
“…The zirconium acts as catalyst and carbon covers the surface of growing grains, serving as new nucleation sites. Thus, grain growth is hindered and growth proceeds by continuous renucleation [13,26,31].…”
Section: Grains Sizementioning
confidence: 99%
“…For such application, the coatings are required to be not only chemically stable, in order to produce biocompatible materials, but must also possess good mechanical, tribological and antibacterial properties to prevent implant failure [4]. On this basis, the Me-CN system has been proposed and extensively studied to produce coatings to improve the mechanical and tribological properties of base materials such as SS316L, TiAlV and Ti, among others [5][6][7]. M. Balaceanu et al [8], for example, studied ZrCN coatings to optimize the 316L stainless steel protection for medical implants, concluding that an enriched biocompatibility and remodeling process was exhibited, causing a negligible inflammatory response.…”
Section: Introductionmentioning
confidence: 99%